Sistem pengelolaan sampah padat di ruang IGD RSUP Fatmawati Jakarta tahun 2018 - Delika Putri; Thresya Febrianti (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
Solid waste management system in the IGD room of Fatmawati Hospital, Jakarta in 2018Purpose: The purpose of the study was to see an overview of the medical solid waste management system in the Emergency Room of Fatmawati Hospital. This research is a qualitative descriptive study.Method: Data collection is done by in-depth interviews, observation and document review. The informants in this study were consisting of the Head of the Sanitation Installation Sub Department Fatmawati Hospital seven people, Solid Waste Management Staff, Cleaning Services, Nurses, and Second Parties (Vendors). This research was conducted in October-November 2018 at Fatmawati General Hospital. The variables examined from the input to the output of the solid waste management process.Results: The results of the study showed that the management of solid waste from facilities and was running normally.Conclusion: The amount of solid waste is 4 tons/day. The waste management in accordance with Minister of Health Regulation No.1204/MENKES/SK/X2004 except in the selection and transportation of medical waste.